Prevalence and inconformity of refractive errors and ocular biometry of 3573 medical university freshman students for 4 consecutive years - Hui-Juan Gao (International Journal of Ophthalmology, 2022)
AIM: To evaluate the prevalence of refractive errors and ocular biometry in 3573 freshman students at Tianjin Medical University for 4 consecutive years. METHODS: In this university-based, cross-sectional study, comprising 3573 students, visual acuity (VA), slit-lamp examination, non-cycloplegic auto-refraction, and ocular biometry were recorded. RESULTS: The prevalence of myopia increased annually, from 2017 to 2020 were 93.5%, 94.5%, 95.9%, and 96.2%, respectively (P=0.03), and the prevalence of high myopia was 25.7%, 26.9%, 28.6%, and 28.6%, respectively. Males tended to have a higher percentage of total astigmatism than females, with astigmatism ≥0.75 and ≥1.0 D criteria. The percentage of with-the-rule astigmatism, against-the-rule astigmatism, and oblique astigmatism was 90.3%, 5.8%, and 3.9%, respectively, with astigmatism ≥1.00 D criteria. The mean spherical equivalent, axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), corneal radius (CR), and lens position (LP) were 4.37±2.52 D, 25.28±1.24 mm, 539.49±34.98 μm, 3.31±0.34 mm, 3.47±0.21 mm, 7.8±0.28 mm, and 5.04±0.32 mm, respectively. With diopter increase in myopia, the AL became longer, CR became steeper, ACD became deeper, LT became thinner, and LP became more posterior (all P<0.01). Females had a shorter AL, thinner CCT, smaller CR, shallower ACD, thicker lens, and more anterior LP than males (P<0.01). The 64% of high myopia had AL≥26 mm, meanwhile, 5.8% mild myopia and 21.1% moderate myopia had AL≥26 mm. With AL≥26 mm, mild and moderate myopia compared to high myopia, AL was shorter (26.51±0.46 vs 26.87±0.70 mm), CR was larger (8.10±0.3 vs 7.85±0.23 mm) and LT was thinner (3.39±0.19 vs 3.45±0.19 mm, P<0.001). CONCLUSION: The prevalence of myopia and high myopia is significantly high in freshman students. The majority of astigmatism is with-the-rule. Inconformity of refractive errors and ocular biometry existed in some students. Attention should be paid to the ocular biometry of myopia.